IMPLEMENTASI KEBIJAKAN KEIMIGRASIAN PADA STATUS KEWARGANEGARAAN GANDA : STUDI PADA KANTOR IMIGRASI KELAS I NON TPI PATI - Yoreyke Adevia Santoso; Najamuddin Khairur Rijal (Universitas Gorontalo, 2022)
This study aims to analyze the immigration policy on dual citizenship status in the Immigration Office Class 1 Non TPI Pati. Dual citizenship itself is an Indonesian government policy for children born from mixed marriages between Indonesian citizens and foreign citizens. Citizenship is regulated in Law No. 12 of 2006, in mixed marriages, children will get limited dual citizenship, namely up to 18 years and no later than 21 years who are registered as dual citizenship children and receive a certificate or affidavit card. This study uses a normative juridical approach. The data analysis technique used in this study is qualitative with secondary data collection techniques from various sources, both journals, news, thesis, and also conducting direct interviews with the Pati immigration office employees regarding limited dual citizenship. The concept used by the author is the concept of dual citizenship as a tool to analyze and find out about the implementation of immigration policies on dual citizenship status in the Immigration Office Class 1 Non TPI Pati.